The function f(x) = 3x + 6.

First, find the inverse function `f^-1(x)`

y = f(x) = 3x + 6

=> 3x = y - 6

=> x = (y - 6)/3

interchanging x and y gives y = (x - 6)/3

=> `f^-1(x) = (x - 6)/3`

f(x) =...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The function f(x) = 3x + 6.

First, find the inverse function `f^-1(x)`

y = f(x) = 3x + 6

=> 3x = y - 6

=> x = (y - 6)/3

interchanging x and y gives y = (x - 6)/3

=> `f^-1(x) = (x - 6)/3`

f(x) = 3x + 6 has real values for all values of x lying in R. The domain of the function is R. Also, f(x) can take all values in R for x lying in R. Similarly, it can be seen that (x - 6)/3 gives a real value for all real values of R. And (x - 6)/3 can take all values in R if x is real. Therefore the range and domain of both f(x) and `f^-1(x)` is R.

**The inverse** `f^-1(x) = (x - 6)/3` **. The range and domain of f(x) and** `f^-1(x)`** is R**